Sequencing and Transcriptional Analysis of the Streptococcus thermophilus Histamine Biosynthesis Gene Cluster: Factors That Affect Differential hdcA Expression - Calles-Enríquez, Marina (American Society for Microbiology (ASM), 2010)
Histamine, a toxic compound that is formed by the decarboxylation of histidine through the action of microbial decarboxylases, can accumulate in fermented food products. From a total of 69 Streptococcus thermophilus strains screened, two strains, CHCC1524 and CHCC6483, showed the capacity to produce histamine. The hdc clusters of S. thermophilus CHCC1524 and CHCC6483 were sequenced, and the factors that affect histamine biosynthesis and histidine-decarboxylating gene (hdcA) expression were studied. The hdc cluster began with the hdcA gene, was followed by a transporter (hdcP), and ended with the hdcB gene, which is of unknown function. The three genes were orientated in the same direction. The genetic organization of the hdc cluster showed a unique organization among the lactic acid bacterial group and resembled those of Staphylococcus and Clostridium species, thus indicating possible acquisition through a horizontal transfer mechanism. Transcriptional analysis of the hdc cluster revealed the existence of a polycistronic mRNA covering the three genes. The histidine-decarboxylating gene (hdcA) of S. thermophilus demonstrated maximum expression during the stationary growth phase, with high expression levels correlated with high histamine levels. Limited expression was evident during the lag and exponential growth phases. Low-temperature (4°C) incubation of milk inoculated with a histamine-producing strain showed lower levels of histamine than did inoculated milk kept at 42°C. This reduction was attributed to a reduction in the activity of the HdcA enzyme itself rather than a reduction in gene expression or the presence of a lower cell number.